Progress in the Application of Novel Nanomaterials in Targeted Therapy for Liver Cancer - Wei X; Cao W; Wang S; Zhang Y; Gao Z; Wang S; Yao L; Zhang Z; Li X; Deng W; Xie Y; Li M (International Journal of Nanomedicine)
Xin Wei,1,* Weihua Cao,1,* Shiyu Wang,1,* Yaqin Zhang,1,* Zixuan Gao,1 Shuojie Wang,1 Linmei Yao,1 Ziyu Zhang,1 Xinxin Li,1 Wen Deng,1 Yao Xie,1,2 Minghui Li1,2 1Department of Hepatology Division 2, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People’s Republic of China; 2Department of Hepatology Division 2, Peking University Ditan Teaching Hospital, Beijing, 100015, People’s Republic of China*These authors contributed equally to this workCorrespondence: Minghui Li; Yao Xie, Email wuhm2000@sina.com; xieyao00120184@sina.comAbstract: In recent years, nanobiotechnology, widely used in hepatoma, holds great promise for improving targeted hepatocarcinoma therapy. On account of the unique properties of low toxicity, good tolerance, biocompatibility, and biodegradability of new nanomaterials, a targeted drug delivery system (TDDS) has been constructed, which can boost the therapeutic effect of hepatoma-targeted drugs, reduce drug toxicity, and minimize off target reactions by enhancing permeability retention effect (EPR) and active targeting, thus improving existing liver cancer targeted therapy strategies. Different nanoparticles have their own advantages and disadvantages. They can be loaded with multiple drugs on the same nanoparticle and can also be surface modified with each other to achieve synergistic anti-tumor effects. This essay provides a comprehensive overview of the current status of targeted therapy for hepatocarcinoma, nanoparticles’ structure, advantages and disadvantages of each nanoparticle, and the application progress of nanoparticles in targeted therapy for liver cancer. We hope to provide a basis for the future clinical targeted therapy of hepatoma using nanotechnology. Keywords: liver cancer, targeted therapy, nanotechnology, drug delivery, nanoparticles